Site selection for shrimp culture in Basrah, Iraq - Ghazi, Abdulhussein H.; Ali, Malik H.; Al–Noor, Sajed S. (Iraqi Journal of Aquaculture, 2021)
In this study, several region and sites were investigated for the most appropriate site for shrimp culture in Basrah province/Iraq. An index values based on 8 indicators revealed hat the area located at the East Basrah channel is the best (excellent) for shrimp culture.